2021
DOI: 10.3390/ijerph18020577
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Alterations in Cardiac DNA Methylation in Adult Mice by Perinatal Lead Exposure

Abstract: Environmental factors play an important role in the etiology of cardiovascular diseases. Cardiovascular diseases exhibit marked sexual dimorphism; however, the sex-specific effects of environmental exposures on cardiac health are incompletely understood. Perinatal and adult exposures to the metal lead (Pb) are linked to several adverse cardiovascular outcomes, but the sex-specific effects of this toxicant on the heart have received little attention. Perinatal environmental exposures can lead to disease through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 88 publications
1
14
0
Order By: Relevance
“…Few studies, however, have investigated the effects of Pb on the cardiac epigenome. We recently discovered that perinatal Pb exposure results in sex-specific changes in DNA methylation in the hearts of offspring mice that are present in adulthood, long after cessation of the exposure [ 146 ]. The implications of these changes for cardiac health are under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies, however, have investigated the effects of Pb on the cardiac epigenome. We recently discovered that perinatal Pb exposure results in sex-specific changes in DNA methylation in the hearts of offspring mice that are present in adulthood, long after cessation of the exposure [ 146 ]. The implications of these changes for cardiac health are under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…At weaning on postnatal day 21, approximately 1 male and 1 female offspring per litter (n = 7 mice per condition) were sacrificed for tissue harvest. A second cohort of mice (approximately 1 male and 1 female per litter) was sacrificed at 5 months of age (n = 6 mice per condition), and data from these mice have been published previously [ 44 ]. All animals had access to food and drinking water ad libitum throughout the experiment while housed in polycarbonate-free cages.…”
Section: Methodsmentioning
confidence: 99%
“…Enhanced Reduced Representation Bisulfite Sequencing (ERRBS) was utilized to examine changes in DNA methylation with Pb exposure in this study (N = 7 per sex, per condition). Our previously published study of animals at 5 months of age included 6 animals per sex, per condition [ 44 ]. ERRBS permits the quantitative detection of base-pair resolution DNA methylation at CpG-rich regions in the genome [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pb is a known neurotoxic substance that may impair spatial learning and memory by damaging hippocampal long-term enhancement (LTP) and damage hippocampal neurons [ 2 ]. Pb exposure has been linked to high blood pressure, myocardial infarction, stroke, and arrhythmias in humans and animals [ 3 ]. It has been found that Pb exposure may cause cellular oxidative stress, ECG abnormalities, and elevated blood pressure, which may cause cardiovascular disease [ 4 ].…”
Section: Introductionmentioning
confidence: 99%